A past misremembered? depictions of Jewish persection under National Socialism in East German cinema - Ward, Elizabeth Margaret (2014)
Throughout its existence, East Germany's ruling Sozialistische Einheitspartei Deutschlands (SED) never officialy acknowledged any direct or inherited responsibility for the crimes committed on its territory between 1933 and 1945, instead choosing to recast itself ab booth victim and victor of fascist oppression through the foregrounding of political persecution. This interpretative framework undoubtedly resulted in the marginalisation of the fate of Jews under National Socialism in East German historiography and memories of the past. However, by focusing on East German cinematic engagements with National Socialist racial persuetion, i seek to challenge the assertion that films depicting Jewish victimhood were unwelcome or even taboo in the German Democratic Republic. By combining close readings of five films - Ehe im Schatten (Maetzig, 1947) Sterne (Wolf, 1959), Lebende Ware (Luderer, 1966), Jakob der Lügner (Beyer, 1974) and Die Schauspielerin (Kühn, 1988) - with an analysis of the films' production files, i unravel the complex status of films dealing with Jewish perseuction produces in a country which consistently priviled narratives of political persecution abrove racial victimhood.
Keywords: Hochschulschrift